2021
DOI: 10.3389/fmed.2021.785327
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid and Risk of Chronic Heart Failure: A Systematic Review and Meta-Analysis

Abstract: Objectives: A systematic review and meta-analysis was performed to evaluate the potential prognostic role of serum uric acid (SUA) in patients with chronic heart failure (CHF).Methods: The Embase, PubMed, Web of Science and Cochrane Library databases were searched up to 5 April 2021 for relevant publications. Random effects model was used to pool data. STATA15.0 software was used to perform meta-analysis. Heterogeneity was assessed using the Cochran Q statistic (significance level of P < 0.10) and I2 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Hyperuricaemia is commonly observed in HF and has been established as an independent predictor of increased risk of HF hospitalisations and death by several studies. [5][6][7] Not only is hyperuricaemia a predictor of poor prognosis in HF populations, studies have showed that UA predicts incident HF with both preserved 12 and reduced ejection fraction. [13][14][15][16] There also seems to be a concentration-effect relationship between UA levels and risk of incident HF, and Huang et al showed in a metaanalysis, that for every 1 mg/dL increase in UA, the odds of developing HF increase by 19%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hyperuricaemia is commonly observed in HF and has been established as an independent predictor of increased risk of HF hospitalisations and death by several studies. [5][6][7] Not only is hyperuricaemia a predictor of poor prognosis in HF populations, studies have showed that UA predicts incident HF with both preserved 12 and reduced ejection fraction. [13][14][15][16] There also seems to be a concentration-effect relationship between UA levels and risk of incident HF, and Huang et al showed in a metaanalysis, that for every 1 mg/dL increase in UA, the odds of developing HF increase by 19%.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricaemia is commonly observed in HF and has been established as an independent predictor of increased risk of HF hospitalisations and death by several studies 5–7. Not only is hyperuricaemia a predictor of poor prognosis in HF populations, studies have showed that UA predicts incident HF with both preserved12 and reduced ejection fraction 13–16.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through post-hoc analysis of the GISSI-HF trial, the 3rd serum uric acid tertile (> 7.2 mg/dl) had a nearly 1.8-fold increased risk of both allcause death and cardiovascular death in chronic HF patients 9 . A meta-analysis of 18 studies with over 33,000 sample sizes suggest SUA is positively associated with the risk of all-cause mortality, cardiovascular death and combined death or cardiac events in CHF patients 10 . Arslan and teams found UA combined with NT-proBNP seemed to be a stronger predictor for all-cause mortality and HF hospitalization 11 .…”
Section: Introductionmentioning
confidence: 99%